2023
DOI: 10.1101/2023.07.05.546622
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Novel co-culture strategies of tumor organoids with autologous T-cells reveal clinically relevant combinations of immune-checkpoint and targeted therapies

Abstract: Patient-derived tumor organoids (PDTOs) have become relevant pre-clinical models for therapeutic modeling since they highly recapitulate patients' responses to treatment. Nevertheless, their value for immunotherapy modeling has not been fully explored. We developed a tumor processing protocol that enables the establishment of PDTOs and tumor-infiltrating lymphocytes (TILs) isolation. By the optimization of functional assays, we compared the T-cells effector functions of matching PBMCs and TILs, demonstrating t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 66 publications
0
2
0
Order By: Relevance
“…Our studies in mouse T cells showed a potent ability of PPP agonism to induce a TCF1 + progenitor state and combine with checkpoint blockade to yield a significant tumor control and survival benefit. We therefore tested the effects of AG1 in a human immunocompetent patient-derived tumor organoid system 51 , 52 ( Fig. 7G ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our studies in mouse T cells showed a potent ability of PPP agonism to induce a TCF1 + progenitor state and combine with checkpoint blockade to yield a significant tumor control and survival benefit. We therefore tested the effects of AG1 in a human immunocompetent patient-derived tumor organoid system 51 , 52 ( Fig. 7G ).…”
Section: Resultsmentioning
confidence: 99%
“…7G ). Following standard methodologies 51 , 52 , we generated patient-derived tumor organoids (PDTOs) from NSCLC patient specimens. We rapidly expanded 53 T cells from autologous peripheral blood mononuclear cells (PBMCs) donated by the patients for two weeks, either in the presence or absence of AG1 ( Fig.…”
Section: Resultsmentioning
confidence: 99%